An investigation into primary teachers' mental health literacy and resilience in supporting children experiencing mental distress in Aotearoa, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Lawson, Jessicca Kate (Massey University, 2022)
Mental distress is becoming more prevalent amongst children and can impact long-term wellbeing outcomes when left unrecognised and untreated. Primary teachers play an important role in children's development and are key people to help identify and support children experiencing mental distress. In New Zealand there is a gap of baseline information looking at primary teachers' mental health literacy (MHL) and teacher resilience. The present study aims to address this gap by examining primary teacher’s MHL, teacher resilience and perceived level of support when managing student’s mental distress. Applying a mixed-methods design, and gathering data via an online survey, the analysis consisted of both quantitative and qualitative items. The final sample included 508 fully registered New Zealand primary teachers, who had been teaching in New Zealand within the last five years (the G*Power target was 528). The quantitative constructs were statistically analysed using SPSS and qualitative responses through thematic analysis. The measures of MHL and resiliency held strong reliability while perceived support, a construct designed for this survey, did not. The results demonstrated that the level of MHL literacy amongst New Zealand teachers was relatively high compared to peer literature. The level of MHL was positively correlated with teacher resiliency and was statistically higher for teachers with >10 years of teaching experience. There was no observable difference in MHL, teacher resiliency or the relationship between the two when controlling for teaching location (defined as urban and rural teachers). Through the thematic analysis, it was clear that COVID-19 also had a genuine effect on teachers’ level of MHL and resilience. This study confirmed that MHL and resilience is an important topic to teachers with high levels of engagement (despite a lack of statistical power), particularly through the qualitative responses and themes. The evidence that MHL and resiliency is low for new teachers (and appears to build through experience) highlights there is opportunity to do more for younger teachers through education and support. This could include formal mental health training before teachers get into the classroom. Further studies with a powered sample size, qualitative interviews, multiple base line design research, and /or longitudinal studies would build on this research and help provide targeted support for primary teachers to help manage students’ mental distress.
Keywords: 520304 Health psychology